Agrotourism Development in Cibodas Village - Nurhakim, Fitra (Prodi Administrasi Publik FISIP UNPAS, 2023)
Agrotourism development in Cibodas Village represents a substantial shift in the use of agricultural and natural resources in the Tangkuban Perahu Mountains region of West Java. This town has focused on promoting agrotourism as a method for combining natural beauty with local agricultural potential, resulting in memorable tourism experiences while also helping the local community's economic viability. This development also prioritizes teaching and understanding of sustainable agriculture techniques, raising visitor awareness of the significance of environmental conservation and agricultural sustainability. The project aims to determine the process of creating educational agrotourism based on the potential of Cibodas village. This study employs a qualitative method, utilizing a case study methodology.